Tolerance and diversity in Ireland, North and South - Honohan, Iseult, 1951-; Rougier, Nathalie (Manchester University Press, 2016)
This title examines the treatment of cultural and religious diversity -- Indigenous and immigrant -- on both sides of the Irish border to analyse the current state of tolerance and the kinds of policies that need to be developed to respect diversity.